Isolation and examination of A/H5N1 avian influenza virus that caused disease outbreaks in Altai Krai in 2014 - I. A. Chvala; A. V. Andriyasov; N. G. Zinyakov; D. A. Altunin; V. Yu. Sosipatorova (Ветеринария сегодня)
In September, 2014 outbreaks of highly acute infection resulting in high mortality were reported in poultry flocks in some settlements of the Altai Krai. Laboratory tests allowed isolation and identification of highly pathogenic A/H5N1 avian influenza virus. Molecular and biological properties of the virus were examined; typical clinical signs, post-mortem lesions and disease character in chicks were described.